Ten‐year changes in positive and negative marker food, fruit, vegetables, and salad intake in 9–10 year olds: SportsLinx 2000–2001 to 2010–2011. Issue 3 (6th May 2013) - Boddy, L. M.; Abayomi, J.; Johnson, B.; Hackett, A. F.; Stratton, G.
Abstract Background To investigate changes in intakes of 'negative' and 'positive' foods, fruit, vegetables, and salad in serial cohorts of 9–10‐year‐old children from 2000–2001 to 2010–2011. Methods For this serial, cross‐sectional study, children in school year 5 (9–10 years of age) completed the SportsLinx Lifestyles Survey [n = 30 239 (15 336 boys and 14 903 girls)]. Changes in positive and negative food scores, and the proportion of boys and girls reportedly consuming fruit, vegetables and salad on the previous day to surveying, were investigated annually from 2000 to 2011. Results The consumption of negative foods declined and positive foods increased significantly compared to baseline. Positive changes in fruit, vegetables and salad consumption were observed over time, with the most recent cohort more likely to consume fruit, vegetables and salad compared to the 2000–2001 baseline. Girls displayed more favourable positive and negative food scores and were more likely to consume fruit, salad and vegetables across several study years compared to boys. Conclusions The consumption of negative and positive foods, fruit, vegetables, and salad has improved over the last 10 years. In addition, girls appear to have better positive and negative food scores, and were more likely to consume fruit, vegetables and salad, across a number of study years or cohorts compared to boys. These encouraging findings suggest that children's food intake has improved since 2000. Furthermore, the data indicate that boys and girls may require separate or different healthy eating messages to further improve food intake.